Virus-specific CD8+ T cells upregulate programmed death-1 expression during acute friend retrovirus infection but are highly cytotoxic and control virus replication - Zelinskyy, Gennadiy; Myers, Lara; Dietze, Kirsten K.; Gibbert, Kathrin; Roggendorf, Michael; Liu, Jia; Lu, Mengji; Kraft, Anke R.; Teichgräber, Volker; Hasenkrug, Kim J.; Dittmer, Ulf (The journal of immunology, 2011)
It was recently reported that inhibitory molecules such as programmed death-1 (PD-1) were upregulated on CD8+ T cells during acute Friend retrovirus infection and that the cells were prematurely exhausted and dysfunctional in vitro. The current study confirms that most activated CD8+ T cells upregulated expression of PD-1 during acute infection and revealed a dichotomy of function between PD-1hi and PD-1lo subsets. More PD-1lo cells produced antiviral cytokines such as IFN-γ and TNF-α, whereas more PD-1hi cells displayed characteristics of cytotoxic effectors such as production of granzymes and surface expression of CD107a. Importantly, CD8+ T cells mediated rapid in vivo cytotoxicity and were critical for control of acute Friend virus replication. Thus, direct ex vivo analyses and in vivo experiments revealed high CD8+ T cell functionality and indicate that PD-1 expression during acute infection is not a marker of T cell exhaustion.
Gesehen am 22.12.2022
Im Titel ist das "+"-Zeichen hochgestellt